2018 International Conference on Computing, Electronics &Amp; Communications Engineering (iCCECE) 2018
DOI: 10.1109/iccecome.2018.8659275
|View full text |Cite
|
Sign up to set email alerts
|

Software Sustainability from A User Perspective A Case Study of A Developing Country (Kingdom of Saudi Arabia)

Abstract: Interest in sustainable development is increasing. Understanding the user's perspective toward software sustainability helps to enhance understanding of the concept. The need for developing countries to enhance their ICT infrastructure to align with UN sustainable development goals increases the necessity to understand the current perception of software users, industry and sustainability experts, to improve the level of software sustainability. Software sustainability has a number of challenges with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Software development firms should utilize sustainable techniques to lower their carbon footprint, since this will have an effect on the environmental aspect of sustainability 80 . Hence, there is a need of standards and guidelines to help people think about sustainability 81 …”
Section: Resultsmentioning
confidence: 99%
“…Software development firms should utilize sustainable techniques to lower their carbon footprint, since this will have an effect on the environmental aspect of sustainability 80 . Hence, there is a need of standards and guidelines to help people think about sustainability 81 …”
Section: Resultsmentioning
confidence: 99%
“…Several studies support the analysis of individual items instead of constructs in these situations. For example, Aljarallah S and Lock R [ 44 ] report on users’ perspective toward software sustainability and present much of their analysis at the item level despite reporting a Cronbach α of <.7 for some of the constructs, while Marchewka JT and Kostiwa K [ 45 ] reported much of their descriptive analysis from a UTAUT-driven questionnaire at an item level after presenting construct level reliability measures. Furthermore, Elo A-L et al [ 46 ] and Clason et al [ 47 ] demonstrated the validity of analyzing individual survey items (not summated).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, sustainability becomes essential to include in software development, and there is a demand for more attention on raising awareness about, and how to innovate, green and sustainable software to support achievement of the SDGs by 2030 . Thus, the identification of software development sustainability requirements is considered a crucial topic that has been investigated and discussed in various countries, such as Brazil [14], [15], Pakistan [16], and Saudi Arabia [17], [18]. According to [19], there is no common understanding about the definition of sustainability in the context of requirements engineering.…”
Section: ) Why Sustainable Software Development?mentioning
confidence: 99%